Desenvolvimento de um sistema de gerenciamento de energia (EMS - Energy Management System) para a rede elétrica inteligente (Smart Grid) - Leite, Jônatas Boás [UNESP] (2015)
This work aims the development of an advanced energy management system to operate the smart grid that comprises the intersection of electrical power system with communication and information technologies. There are, currently, many studies related to the smart grid, which can produce doubts about the smart grid design concept. These doubts are clarified in the first part of this work where novel technologies of smart grid are presented besides the description of the standardization of smart grid design concepts. The use of the smart grid design standard allows identifying and developing all components of the advanced energy management system. The logical components, which require resources of information technology, were developed and implemented in a computational environment, while the physical devices of communication and power systems were meticulously emulated. The electrical devices emulation is based on the probabilistic power flow algorithm that permits both the load fluctuation and the energy market influence. The electrical devices simulator also supports contingency conditions as well as provides electric measurement data to other components of the energy management system. One of these components is the state estimation algorithm that produces the distribution network state using the measurement data. Network states produced by the state estimator are employed in advanced functions of the energy management system like the dynamic coloring, location of non-technical losses and self-healing applications. All proposed methodologies, in this work, were assessed and numerical results demonstrated their efficiencies